From Promise to Proof: Revealing the Comparative Performance of RSV Vaccines Through Network Meta-Analysis - Haq, Hilmi Amirul; Madani, M. Iyad; Abdullah, Bryan Naufal (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Introduction: There is no consensus on the optimal vaccine platform for preventing respiratory syncytial virus (RSV) infection. Recent advances in RSV vaccine development aim to improve efficacy and safety across various platforms. This study aimed to compare the efficacy and safety of available RSV vaccines using a network meta-analytic approach to identify the most effective strategy for RSV prevention.Methods: A systematic search of  PubMed, ScienceDirect, Cochrane, and Scopus (up to November 2025) identified randomized controlled trials (RCTs) of RSV vaccines in healthy populations. Evaluated interventions included Ad26.RSV.preF–RSV preF,  Ad26.RSV.preF, Bivalent RSVpreF, RSVPreF3OA, and placebo controls. Network meta-analyses were performed using the netmeta package in R. Risk of bias and certainty of evidence were appraised using RoB 2.0, CINeMA, and GRADE frameworks, respectively.Result: Ten RCTs were analyzed. Ad26.RSV.preF–RSV preF Protein Vaccine possesses superior efficacy in reducing RSV-related respiratory illness compared to placebo (RR 0.25 [95% CI: 0.15-0.45]).  Ranking analysis corroborated this finding, identifying it as the most effective intervention (P-score = 0.827). Safety profiles were comparable across all interventions; however, the precision of these estimates was limited by wide confidence intervals and substantial heterogeneity. Conclusion: Ad26.RSV.preF–RSV preF demonstrated the highest efficacy for RSV prevention. However, their safety profile has not yet been clearly defined, and further research is needed to assess long-term effectiveness and monitor potential late adverse effects.